A organização do espaço urbano e a estrutura térmica da cidade de Cuiabá-MT - Ferreira, Hugo Vilela Lemos (2019)
In the urban climate, problems related to the thermal structure of cities are identified, which condition situations of human thermal discomfort, mainly. The urban spatial thermal structure is identified as a product of the urban climate thermodynamic subsystem. It is related to the physical properties of the elements of the urban space, which promote local modifications in the atmosphere of the cities. This structure can be analyzed through the configuration of the surface and air temperatures (Ts and Tar respectively, acronyms in Portuguese) of the city in relation to its surroundings and in an intra-urban way. The present work had as general objective to analyze the urban space thermal structure of the city of Cuiabá-MT, Brazil, located in the interior of the South American continent, under the domination of a continental tropical climate alternately humid and dry. For this, general geographical characteristics of the urban site, as well as the organization of the urban space, were analyzed through the mapping of Local Climate Zones (ZCLs, acronym in Portuguese); satellital remote sensing Ts products of the Landsat, ASTER, MODIS and GOES types were analyzed, as well as Tar data in the urban canopy layer; these temperatures data were compared to each other, in seasonal and hourly time scales, and spatial scales, in the urban-rural and intra-urban local context of Cuiabá. The analyzed Ts presented a spatial and temporal variability in it horizontal form and magnitude, related to the characteristics of the organization of the space and the temporality of the climatic conditions. The hot and dry seasonal condition promotes higher temperature amplitudes in nocturnal instants and smaller in diurnal ones; the opposite occurs in the hot and rainy season. It was verified that the Tar relates spatially and in magnitude with the Ts, both covariating with the morphological organization of the space, represented by ZCLs. The built ZCLs of high density presented higher temperatures than those vegetated on the periphery of the city. Amplitudes of just over 10°C between the Ts of built-up areas and the rural surroundings at the same time point were observed. The city center of Cuiabá shows the most heated area of the city compared to areas at the edge of the urban sprawl, with amplitudes of the Tar that exceed 10°C. It was verified that the characteristics of the spatial thermal structure of the city of Cuiabá, manifested in Ts and Tar, reveal spatial facets of the established urban climate.